2008
DOI: 10.1016/j.jallcom.2007.03.094
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ferromagnetic order in URhGe alloyed with Ru, Co and Si

Abstract: We have investigated the evolution of ferromagnetic order in the correlated metal URhGe (Curie temperature T C = 9.5 K) by chemical substitution of Ru, Co and Si. Polycrystalline samples URh 1−x Ru x Ge (x ≤ 0.6), URh 1−x Co x Ge (x ≤ 0.9) and URhGe 1−x Si x (x ≤ 0.2) have been prepared and the magnetic properties have been investigated by magnetization and transport experiments. In the case of Ru doping, T C initially increases, but then decreases linearly as a function of x and is completely suppressed for x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 25 publications
(58 reference statements)
4
32
0
Order By: Relevance
“…This, together with the observation that URhGe is ferromagnetic, prompted the study of URh 1−x Co x Ge alloys (Sakarya et al, 2008), and the final conclusion was that UCoGe is indeed a weak ferromagnet with a Curie temperature near 3 K and a small ordered moment of 0.03 µ B (Huy et al, 2007b). The transition was found to be weakly first order by means of nuclear quadrupole resonance measurements (Hattori et al, 2010).…”
Section: Uranium-based Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, together with the observation that URhGe is ferromagnetic, prompted the study of URh 1−x Co x Ge alloys (Sakarya et al, 2008), and the final conclusion was that UCoGe is indeed a weak ferromagnet with a Curie temperature near 3 K and a small ordered moment of 0.03 µ B (Huy et al, 2007b). The transition was found to be weakly first order by means of nuclear quadrupole resonance measurements (Hattori et al, 2010).…”
Section: Uranium-based Compoundsmentioning
confidence: 99%
“…m Pressure decreases TC (Slooten et al, 2009); TCP not accessible. TC increases nonmonotonically upon doping with Rh (Sakarya et al, 2008); order of transition for URhxCo1−xGe not known except for x = 1 (2nd order with TC = 9.5 K). n Inferred from existence of tricritical wings.…”
mentioning
confidence: 99%
“…Isostructural compounds URhGe and UCoGe, which crystallize in a TiNiSi-type structure naturally fulfill this condition, and the coexistence of ferromagnetism (FM) and SC has been discovered here 8,9) . Both FM and SC can be affected by alloying [10][11][12][13][14] , the application of a magnetic field 15,16) , and the external pressure [17][18][19] . The resulting H-T-p-x phase diagrams corroborate the close connection between FM and SC.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported the evolution of ferromagnetic order in URhGe upon replacing Rh by Ru or Co, or Ge by Si [14]. This work was motivated by the possibility to attain a ferromagnetic quantum critical point in URhGe by doping.…”
Section: Introductionmentioning
confidence: 99%
“…Notice, in the literature it was initially reported that UCoGe has a paramagnetic ground state [11,15]. Magnetization data taken on polycrystalline samples with x = 0.0, 0.2, 0.4, 0.6, 0.8 and 0.9 revealed that the Curie temperature (T C = 9.5 K for x = 0.0) increases up to T C = 20 K for x = 0.6, and then drops to 8.0 K for x = 0.9 [14]. These data hinted at a ferromagnetic instability for x d 1.0, but later experiments surprisingly showed ferromagnetism survives in the URh 1-x Co x Ge alloys up to x = 1.0 [2].…”
Section: Introductionmentioning
confidence: 99%